2009
DOI: 10.1109/tmag.2008.2010655
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of PFPE Lubricants on Magnetic Disks

Abstract: Perfluoropolyether lubricant films on magnetic disks were observed by means of atomic force microscopy (AFM) with a fluoridecoated probe. The lubricant films could be observed directly because the adhesion force was decreased by the anti-wetting effect of the fluoride coating on the probes. We compared the molecular conformation of Z-dol (Mw: 2000, 3000, 6000, 8000) with that of Z-tetraol. Thus, we found that the film coverage of a lubricant with high molecular weight exhibited varying (i.e., higher and lower)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The shoulder height was *1.7 nm. This value was in good agreement with the step height of Z-tetraol2000 obtained by AFM direct observation; it is suggested that this shoulder height corresponds to a monolayer film thickness of Z-tetraol2000 [8]. Figure 7 shows the spreading profiles of TA-30 which were measured by varying the disk substrate temperature from 20 to 80°C.…”
Section: Afm Observation Resultssupporting
confidence: 84%
“…The shoulder height was *1.7 nm. This value was in good agreement with the step height of Z-tetraol2000 obtained by AFM direct observation; it is suggested that this shoulder height corresponds to a monolayer film thickness of Z-tetraol2000 [8]. Figure 7 shows the spreading profiles of TA-30 which were measured by varying the disk substrate temperature from 20 to 80°C.…”
Section: Afm Observation Resultssupporting
confidence: 84%
“…Therefore, Z-dol of experimental samples had double layers, approximately 1.2 nm, and that of Z-tetraol was approximately 1.7 nm [12] and only Z-tetraolt with 2.0 nm had double layers. It was estimated that the lubricant film with the double layers showed the stable second regime, because the second layer molecules on the first layer might add the hydrodynamic lubrication effect.…”
Section: A Slider Vibration Measurementsmentioning
confidence: 89%
“…Z-tetraol showed smaller TDPs and similar slope compared to Z-dol, when the lubricant thickness was thinner than 1.6 nm. This difference of TDPs was estimated to be affected from the difference of the lubricant film structure, because the monolayer thickness of Z-dol was approximately 1.1-1.2 nm [12].…”
Section: A Slider Vibration Measurementsmentioning
confidence: 99%
“…The AFM probes were dipped into the solution (30 wt% concentration). This fluoride-coated probe was used to scan the surface of the lubricant film and measured the step height at the boundary of the lubricant film [7]. The step height corresponded to the molecular height of the lubricant monolayer.…”
Section: Afm Observationmentioning
confidence: 99%